Organophosphorus compound poisoning in newborn - Kumar, Poornima; Sanketh, R; Krishnan, Lalitha (Indian Journal of Child Health, 2015)
Poisoning is a diagnosis seldom made in neonatal intensive care units as most clinical features such as lethargy, respiratory distress, and poor feeding mimic common neonatal conditions. An 8-day-old male baby presented with complaints of inconsolable crying, poor feeding, and seizures for 1 day. On admission, he had bradycardia, copious secretions and pin-point pupils, which led to suspicion of cholinergic over-activity. Cholinesterase levels were 2209 IU/L in baby which increased to 5936 IU/L on day 18 of life. There was a history of charred vasambu (Acorus calamus) being applied over the tongue. Contamination of vasambu with organophosphates was suspected which was confirmed by high performance thin layer chromatography analysis showing chlorpyrifos derivatives. Baby improved gradually with supportive treatment and was discharged on day 18 of life.